Farmers Behavior on Market Product of Magelang (Duck to Induce Creative Economy in Ngadirojo Village, Secang District - Rahma Wulan Idayanti; Ayu Rahayu; Shinta Ratnawati; Nurul Anindyawati (Universitas Tidar, 2020)
Magelang ducks are one of Magelang's native germplasm that has not received serious attention from society. Magelang duck products are expected to have portions in societies' protein needs and the economy's value to make additional income. This research aimed to analyze Magelang duck farmers' behavior on marketing Magelang duck products, either the eggs or meat from cast-off ducks, to induce local farmers' creative economy. This research was held in Ngadirojo village, Secang subdistrict, Magelang district, from January to February 2020. Samples used were local farmers selected on purpose or purposive random sampling. They were 30 persons of farmers. The farmers selected were based on the total livestock owned in Ngadirojo. The method used in this research were survey, interview, and direct observation. Variables observed were farmers' behavior on marketing the livestock product, behavior on marketing the processed product of Magelang ducks, behavior on using marketing channel, and price determinations using a questioner observed by Likert scale. The data collected were analyzed using the z-test. The result showed that the level of farmers behavior on marketing the Magelang duck products either on eggs and meat from cast-off ducks were 95%, behavior on marketing the harvests of Magelang duck as a processed product were 0%, and behavior of the selling method and the price determination of Magelang duck were 81.4%. It is expected that the result of this marketing behavior identification can induce the development of the Magelang duck creative economy and provide positive effects on farmer's additional income.Keywords: Behavior, Livestock product, Magelang duck.